2002
DOI: 10.1037/1089-2680.6.2.166
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Suppression of Female Sexuality

Abstract: Four theories about cultural suppression of female sexuality are evaluated. Data are reviewed on cross-cultural differences in power and sex ratios, reactions to the sexual revolution, direct restraining influences on adolescent and adult female sexuality, double standard patterns of sexual morality, female genital surgery, legal and religious restrictions on sex, prostitution and pornography, and sexual deception. The view that men suppress female sexuality received hardly any support and is flatly contradict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
200
3
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(216 citation statements)
references
References 62 publications
3
200
3
10
Order By: Relevance
“…Our data also add context to a growing body of literature documenting the importance of men's emotional connection to their sexual partners 13,14 and women's experiences of sexual desire and sexual pleasure. 41 Pertinent to the latter, we found that all motivations exerted a stronger influence on partnered behavior for women as compared to men, particularly in terms of a woman's wanting to have sex or perceiving that her partner wanted to have sex. These findings parallel recent qualitative work demonstrating the variance of gendered sexual scripts in relationship and individual contexts.…”
Section: Discussionmentioning
confidence: 75%
“…Our data also add context to a growing body of literature documenting the importance of men's emotional connection to their sexual partners 13,14 and women's experiences of sexual desire and sexual pleasure. 41 Pertinent to the latter, we found that all motivations exerted a stronger influence on partnered behavior for women as compared to men, particularly in terms of a woman's wanting to have sex or perceiving that her partner wanted to have sex. These findings parallel recent qualitative work demonstrating the variance of gendered sexual scripts in relationship and individual contexts.…”
Section: Discussionmentioning
confidence: 75%
“…Este aspecto es importante ya que existe un debate entre investigadores sobre si la doble moral tiene su origen en las actitudes de los varones o de las mujeres. Desde el enfoque que defiende que las mujeres tienen mayor adhesión a la doble moral se afirma que éstas tendrían mayor poder sobre la relación, pero lo utilizarían para evitar la actividad sexual (Baumeister y Twenge, 2002). Prueba de ello, es que las mujeres, con alta adhesión a la doble moral, con mayor frecuencia se mantienen abstinentes sexualmente y son más reacias a hablar de aspectos relacionados con la sexualidad (Jackson y Cram, 2003;Leftkowitz, Boone y Shearer, 2004).…”
Section: Introductionunclassified
“…On the other hand, the need of belongingness can just be meeting in pleasant or satisfactory relationships. Baumeister and Twenge [3] also claim that, belongingness positively affects the health and well-being. Physical and psychological problems are commonly seen in the case of unsatisfied need of belongingness.…”
Section: Introductionmentioning
confidence: 99%
“…Baumeister and Twenge [3] suggest that need to belong is a very powerful motive which leads people to have social attachments and to form and maintain enduring interpersonal relationships. Having a long-term intimate relationship generally produces positive emotions.…”
Section: Introductionmentioning
confidence: 99%